2010
DOI: 10.1158/1940-6207.capr-10-0035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Sonic Hedgehog Pathway Affect Clinical Outcomes in Non–Muscle-Invasive Bladder Cancer

Abstract: Sonic hedgehog (Shh) pathway genetic variations may affect bladder cancer risk and clinical outcomes. Therefore, we genotyped 177 single-nucleotide polymorphisms (SNP) in 11 Shh pathway genes in a study including 803 bladder cancer cases and 803 controls. We assessed SNP associations with cancer risk and clinical outcomes in 419 cases of non-muscle-invasive bladder cancer (NMIBC) and 318 cases of muscle-invasive and metastatic bladder cancer (MiMBC). Only three SNPs (GLI3 rs3823720, rs3735361, and rs10951671) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…However, despite a large body of work, reliable molecular markers and reliable molecular therapeutic targets have not been identified [16]. Several recent studies have focused on the role of the hedgehog/Gli signal transduction pathway in carcinogenesis of TCC [6,7]. The hedgehog pathway operates in organogenesis, control of proliferation, and the differentiation of embryonic and adult stem cells, thus, not surprisingly, it has been linked with several different tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite a large body of work, reliable molecular markers and reliable molecular therapeutic targets have not been identified [16]. Several recent studies have focused on the role of the hedgehog/Gli signal transduction pathway in carcinogenesis of TCC [6,7]. The hedgehog pathway operates in organogenesis, control of proliferation, and the differentiation of embryonic and adult stem cells, thus, not surprisingly, it has been linked with several different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Chen etal. [7] examined genetic variations in the hedgehog pathway in a large group of patients with bladder cancer in Texas. These investigators genotyped 177 single nucleotide polymorphisms (SNPs) in 11 hedgehog pathway genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, many authors suggested that HHSP can be activated in later stages of diseases in which HHSP activation has been shown to correlate with lower RFS and bad OS [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Although perhaps less advanced than this global approach in a phase-III clinical trial, genotyping work in other sites, including the colorectum (aspirin, celecoxib, statins), prostate (selenium), and bladder (BCG), is beginning to make headway toward personalized cancer prevention as well (26)(27)(28)(29). Similar personalized genotyping approaches are being applied in research in tobacco dependence (30) and cancer therapy (31).…”
mentioning
confidence: 99%